Analisis Blockchain untuk Otentikasi Transaksi pada Sistem Pembayaran Digital - Viorella Natalya Simanjuntak; Joitanata Saragi; Aditya Rizqy Bakhtiar; Vuza Roinda Br Sihombing; Zalsa Nabilla Rosa Dalimunthe; Yohana Adelia Nugroho; Wilfy Hardi Napitupulu; Sudarto Sudarto (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
This study aims to analyze the implementation of blockchain technology in enhancing the security and authentication of transactions in digital payment systems. The method employed is a Systematic Literature Review (SLR) of 21 accredited national and international journals published between 2020 and 2025. The SLR process involved the stages of identification, selection, quality assessment, and synthesis of literature relevant to the research topic. The results indicate that blockchain technology is capable of improving the security, transparency, and efficiency of digital payment systems through decentralized and tamper-resistant transaction recording mechanisms. The application of smart contracts has proven effective in verifying transaction authenticity without the involvement of third parties, while simultaneously reducing operational costs. Nevertheless, challenges such as inadequate regulatory frameworks, limited infrastructure, and low levels of digital literacy remain significant barriers to the widespread adoption of blockchain in Indonesia. In conclusion, blockchain has the potential to serve as a critical foundation for the development of a secure and trustworthy digital payment ecosystem, with opportunities for future research focusing on the integration of Artificial Intelligence (AI) and the Internet of Things (IoT) to further enhance the efficiency and reliability of digital payment systems.